Analisis Determinasi Kinerja Reksa Dana Pendapatan Tetap di Indonesia Periode 1999-2003 (Penggunaan Model Jensen dan Model Gudikunst) - Jerry Dennis P; Adler H. Manurung; Nachrowi D. Nachrowi (The Indonesian Journal of Accounting Research, 2013)
The objective of this research is to evaluate Bond Mutual Fund Performance in Indonesia and determine some variables that can affect Mutual Fund Performance. Mutual Fund Performance can be measured by using Jensen Model (1968) and Gudikunst Model (1992). The information about bond selection and market timing ability can be measured by using Henriksson - Merton Model (1981). Using Philpot Model (1998), this research examine Mutual Fund attributes that can determine Mutual Fund Performance. Finally, the results show that Bond Mutual Fund have been unable to outperform the market index on a risk-adjusted return basis. The market excess return shows surprising strength relationship to the portfolio excess return.  Generally the sample of Bond Mutual Fund in this research show that portfolio manager has arbitrage opportunity to increase portfolio excess return due to wide range in yield spread, manage in large total asset size and conduct with passive strategy in their portfolio management. This underperform of Bond Mutual Fund Performance can be happened because portfolio managers do not have superiority skills in market timing and bond selection and also the differences of each Bond Mutual Fund attributes.